Lived Experiences and Motivating Factors of Online Commercial Sex Work Among Adolescents: A Phenomenological Qualitative Study - Saidah, Qori Ila; Puji, Hastuti; Elma , Irnanda (Journal of Applied Nursing and Health, 2026)
Background: Online commercial sexual activity among adolescents is an emerging public health concern in low- and middle-income countries (LMICs), increasing risks of sexually transmitted infections, unintended pregnancy, and psychosocial harm. This issue is highly relevant to nursing and community health practice, particularly in prevention and early identification efforts. However, the psychosocial and environmental factors driving adolescents to engage in online commercial sex remain insufficiently explored, especially within LMIC contexts. Therefore, this study aims to analyze the factors influencing adolescents’ involvement in online commercial sexual activities. Methods: This is a phenomenology research. The population in this study were adolescents and young age who made online worker of commercial sex in Surabaya region. The sample was five teenager with inclussion criteria aged 18-23 years old, using platform to offering sexual commercial and agree to share their experience selected with purposive sampling. Data were collected through in-depth interviews and recording and use data analize with Colaizi’s approach. Research team, study design, analysis and finding are stricly align with Consolidated Criteria for Reporting Qualitative Research (COREQ) standards. Results: There are five themes have been founded in this study. Most paticipantss engaged in online commercial sex due to economic and lifestyle factors. The income earned through online commercial sex was considered sufficient to support their lifestyle. This led to addiction, both economically and for pleasure, leading to continued online commercial sex activity. Conclusion: This study highlights three key factors influencing online commercial sex activity among adolescents. Economic incentives emerged as the primary driver, particularly in fulfilling lifestyle-related needs, while perceived enjoyment also motivated engagement. These findings underscore the need for targeted prevention strategies that address adolescents’ economic vulnerability, strengthen family communication, and develop digital-based health promotion and policy interventions to mitigate online sexual risk behaviors.